Pendekatan Filosofis terhadap Norma Murabahah: Kajian Ontologi, Epistemologi, dan Aksiologi - Nur Irmandi; Atang Abdul Hakim; Syamsurijal; Agus Darmawan (STAI Al-Mas'udiyah, 2025)
This study examines the norms of murabahah in the Islamic financial system through a philosophical approach that includes ontology, epistemology, and axiology dimensions. A qualitative approach based on literature studies is used to analyze the nature of murabahah transactions, sources of knowledge about its rules, and ethical values contained in murabahah transactions. Ontologically, murabahah is a transaction that embodies the principle of justice in the sharia economy. From an epistemological perspective, knowledge about murabahah comes from the source of Islamic law interpreted by scholars. Its axiology emphasizes the values of honesty and transparency from the testimony carried out. The results of this philosophical study are expected to provide a deeper understanding of the development and application of murabahah in modern sharia economic practices.